Pemberdayaan Perangkat Desa dan UMKM Desa Tawangsari Mojokerto melalui Workshop YouTube dan Desain Visual - Rohmat Hidayat; Siti Sufaidah; Nurul Afidah; Yuyun Bahtiar; Muhammad Dliyaurrahman Muzakki; Rendy Choiruddin; Fitrotuzzahwannisa Fitrotuzzahwannisa; Aisyatul Izzah Putri Aini; Mitayakuna Stianto; Octo Gyan Falesta (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
This community service program was conducted in Tawangsari Village, Trowulan District, Mojokerto Regency, focusing on empowering village officials and local UMKM through digital technology utilization. The main objective was to enhance digital literacy among village officials in managing a YouTube channel as a means of public communication, while strengthening UMKM’ visual identity through logo and banner design. The program applied the Participatory Action Research (PAR) approach, consisting of several stages: needs assessment, planning, workshop implementation, intensive mentoring, and evaluation. The workshop was divided into two sessions, namely YouTube channel management (content creation, video editing, and account management) and visual design (logo and banner production for UMKM products). Evaluation was carried out through pre-test and post-test assessments, satisfaction questionnaires, and portfolio evaluation of participants’ outputs. The results revealed significant improvements in both digital literacy and visual design skills, as indicated by the increase of average scores from 55 to 83 for digital literacy, and from 50 to 80 for visual design. Furthermore, the village officials successfully launched the official YouTube channel of Tawangsari Village, while UMKM actors produced professional logos and banners to represent their product identity. The program not only improved technical skills but also raised awareness of the importance of branding and digital literacy as a strategy for strengthening competitiveness. In conclusion, ICT-based workshops proved effective in strengthening village community capacity. The main recommendation is the need for program sustainability through consistent content publication on YouTube, continuous use of UMKM logos, and advanced digital marketing training to expand market reach.